Transformation of settlement history in the Körös Region in the period between the Late Bronze Age and the end of Iron Age - Bóka, Gergely (Dissertationes Archaeologicae, 2021)
Abstract of PhD thesis submitted in 2020 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Gábor V. Szabó.